Phonetic and phonological perspectives on the acquisition of voice onset time by French-speaking children. - MacLeod, Andrea A. N. (Clinical Linguistics & Phonetics, 2016)
The goal of the present article is to describe the acquisition of the phonetic details and phonological categories of stop consonants in French. To this end, the stop consonants produced by children aged 2–4 years were transcribed and acoustically analysed. Stop consonants provide an interesting window in phonetic and phonological development since they are among the first phonemes to be acquired in French (MacLeod, Sutton, Thordardottir & Trudeau, 2011), yet the mastery of the phonetic detail of these phonemes can be more drawn out (Allen, 1985). The results of the study indicate that these children are producing significant voicing contrasts between homorganic stops using voice onset time, but at the phonetic level their productions are not yet within adult ranges.